Partisipasi Masyarakat Dalam Pendidikan - Analisna Analisna; Sulistiani Sulistiani; Muhammad Yasin (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
The participation of the public, especially the elderly, in improving the quality of education at Nurul Ikhsan School is the focus of this research. In this context, studies on public participation can address various aspects, such as the level of public awareness of educational issues, the role of the community in determining educational policies, and efforts to increase public involvement in improving the education system. Using qualitative research methods with descriptive approaches, data collection methods include observations, systematic and semi-structured interviews of respondents, as well as document analysis. The purpose of research is to acquire new knowledge or discoveries as proof or testing of public participation in education. The problem formula we bring is to explain the characteristics of public involvement in improving the quality of school, increase public engagement, and explain the forms of social participation at school. Through an open and inclusive management approach, parents are involved in the decision-making and implementation of educational programs. Comparisons with traditional management models show that Nurul Ikhsan Schools actively involve parents in decision-making, shared responsibility, and the full exploitation of the potential of society. Forms of social participation of the community in Nurul Ishan School include financial and material contributions, involvement in decision-making, and support in school activities. Through program evaluation and receiving feedback from parents, the school demonstrates its commitment to involving all stakeholders in the management and development of education. Thus, public participation at Nurul Ikhsan School creates close links between schools, students' parents, and the community, strengthening the active involvement of all stakeholders in shaping a better educational future.